A Fuzzy TOPSIS Model to Rank Automotive Suppliers - Amir, Azizi; Aikhuele, Daniel O.; Souleman, Fathi S. (Elsevier Ltd, 2015)
This paper highlights the most significant criteria and sub-criteria in automotive industries for selecting the best supplier from the previous paper. Supplier selection process is one of the key activities of management in a supply chain environment. This paper presents another methodology to select the most suitable supplier in a supply chain system using Fuzzy Technique for Order Performance by Similarity to Ideal Solution (FTOPSIS). Triangular Fuzzy set is applied into the proposed model to handle the vagueness. The interdependencies between criteria are considered. In our FTOPSIS model, the results show that FTOPSIS is remarkably successful in determining the best supplier with stability in the ranking as it relates to the different criteria weights and multiple sub-criteria. The proposed methodology presents a comprehensive multi-criteria approach to find the best ranking among the alternative suppliers. The result shows that supplier A is the best supplier with the Closeness Coefficient of 0.5407. The FTOPSIS model proposed can be apply on other vague multiple criteria decision making problem since it shows good result in the research. Future research may expand the work to another field of study or in a different type of industry.